The Scope of Challenges and Interactions with Foreigners in order to Achieve the Resistance Economy from the Perspective of Qur'an and Ḥadith - Hassan Bozhmehrani; Reza Kohsari; Javad Irvani; Ali Reza Saberian (آموزه‌های قرآنی, 2022)
The expansion of economic interactions between the countries of the world has caused the great affectedness of economic from politics and has paved the way for the pressure of powers on non-aligned countries. On the other hand, the stipulation on the pillar of extraterritorial look (outsourcing) along with internalization in the general policies of the resistance economy indicates the necessity of interaction with other countries to achieve this goal. Considering that economic interactions in the international scene are influenced by the foreign policy of each country, the question arises that: what are the exact criteria and frameworks of challenges and interactions with governments and foreign and non-Muslim societies based on the Qur'an and Sunnah (Arabic: سنة)? In particular, there are challenges in the tradition (Sunnah Arabic: سنة) of the Prophet (ṣallá Allāh ‘alayhi wa-sallam) with polytheists and resistance against their economic sanctions, as well as interaction and agreement. This article, organized by library method and descriptive-analytical method, tries to analyze the prophet’s (ṣallá Allāh ‘alayhi wa-sallam) tradition (Sunnah Arabic: سنة) in this regard while providing the exact course and limits of challenge and interaction, based on the teachings of the Qur'an. The research findings show that the elements of enmity (hostility), hegemony (domination), guardianship [It is explained in the text] and facilitating in Islamic principles (uṣūl) and rules (religious law) determine the limits of interaction and otherwise, the Islamic ruler can have more facilitation and interaction conditioned (depend on) to the observance of public interests.